A VALIDATED STABILITY INDICATING RP-HPLC METHOD DEVELOPMENT FOR ANTI CANCER DRUG ENZALUTAMIDE IN BULK AND PHARMACEUTICALS (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
A reproducible stability-indicating Reverse Phase-HPLC technique for the quantification of enzalutamide in in pharmaceuticals was developed and validated. Chromatography was achieved on Inertsil-ODS-C18 (250mm×4.6 mm) 5µmanalytical column with acetonitrile: methanol: water in 40:30:30% v/v proportion as mobile phase and flow rate of 1 ml/min. Enzalutamide was detected at 237 nm UV-wavelength maximum. In the present work mobile phase used as a diluent. Developed technique was validated over 20-150 µg/ml linear concentration range for enzalutamide. This method established with linearity coefficient value of 0.99 and the percentage recovery was found to be 99.3%. This method was proven with LOD and LOQ values of 0.53 µg/mL and 1.61µg/ml respectively. The drug was degraded in acid and alkaline conditions and the percentage degradation values were 3.10 % and 4.54 % respectively. There was no degradation of drug when exposed to neutral, UV, thermal, sun-light and oxidative conditions.Drug was undergoing degradation when exposed to acid and alkaline conditions. The developed technique was useful in the routine quantitation of enzalutamide.